Child poverty in upper-income countries: Lessons from the Luxembourg Income Study - Janet C. Gornick; Markus Jäntti (Luxembourg Income Study (LIS), 2009)
We draw on LIS' various resources to sketch a portrait of child poverty in upper-income countries. We first summarize past LIS-based scholarship on child poverty, highlighting studies that seek to explain cross-national variation in child poverty levels. Our empirical sections focus on child poverty in 13 upper-income countries. We begin with a descriptive overview of poverty among all households and among those with children, presenting multiple poverty measures (relative and absolute, pre- and post- taxes and transfers) and reporting the magnitude of poverty reduction due to state programs. We focus on within-country associations between child poverty and three important characteristics: family type, parents' educational attainment, and parents' attachment to paid work. Our main conclusions include: (a) child poverty rates vary markedly across the mostly high-income countries included in the LIS data archive; (b) child poverty rates shift over time in diverse ways; (c) within countries, family demography and parents' labor market engagement are the main factors that shape children's likelihood of living in a poor household; (d) taxes and transfers powerfully shape the economic wellbeing of children in all countries; (e) the factors that explain poverty variation within countries are not the same as those that explain poverty variation across countries; the latter are mainly institutional, including both labor market structures and policy configurations.
Keywords: 330; Kinder; Armut; Haushaltseinkommen; Industrieländer